2015
DOI: 10.1242/jeb.128801
|View full text |Cite
|
Sign up to set email alerts
|

Spiders have melanin after all

Abstract: Melanin pigments are broadly distributed in nature -from bacteria to fungi to plants and animals. However, many previous attempts to identify melanins in spiders were unsuccessful, suggesting that these otherwise ubiquitous pigments were lost during spider evolution. Yet, spiders exhibit many dark colours similar to those produced by melanins in other organisms, and the low solubility of melanins makes isolation and characterization difficult. Therefore, whether melanins are truly absent or have simply not yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 29 publications
1
40
0
Order By: Relevance
“…4D). We previously showed that this black colour is produced by eumelanin using Raman spectroscopy (Hsiung et al, 2015a). The Raman signals that we detected must be from eumelanin, not false-positives due to carbonization of burnt specimens, because we only obtained positive Raman signals from black spider body patches, not from nearby regions that were not black (Hsiung et al, 2015a).…”
Section: Blackmentioning
confidence: 52%
See 3 more Smart Citations
“…4D). We previously showed that this black colour is produced by eumelanin using Raman spectroscopy (Hsiung et al, 2015a). The Raman signals that we detected must be from eumelanin, not false-positives due to carbonization of burnt specimens, because we only obtained positive Raman signals from black spider body patches, not from nearby regions that were not black (Hsiung et al, 2015a).…”
Section: Blackmentioning
confidence: 52%
“…The nanomorphology of structural colours has been investigated recently for some spiders (Foelix et al, 2013;Hsiung et al, 2015b;Ingram et al, 2011;Land et al, 2007;Simonis et al, 2013;Stavenga et al, 2016). However, our knowledge of spider pigment biochemistry has remained stagnant for almost 30 years (Holl, 1987, but see Hsiung et al, 2015a). Thus, we still know very little about pigments and the colour production mechanisms of spiders in general.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They, in turn, resemble the Raman spectra of xanthopterin and isoxanthopterin (Saenko et al, 2013;Feng et al, 2001). There is little correspondence with the Raman spectra of melanin, carotene and the simulated spectrum of the ommochrome ommin (Hsiung et al, 2015).…”
Section: Tapetum Structurementioning
confidence: 92%